APPRAISAL SYSTEM REFLECTED IN BO SEO’S ARGUMENTS IN OPEN GRAND FINAL OF THE WORLD UNIVERSITY DEBATING CHAMPIONSHIP 2016 - Kevin Satria Sahida; Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2020)
This study attempts to construe (1) the appraisal devices reflected Bo Seo’s argument, (2) how Bo Seo position arguments that they became viral in debating community. This research belongs to descriptive qualitative. The data in this study is Bo Seo’s argument in the Open Grand Final of World University Debating Championship 2016 Thessaloniki. Furthermore, the data source in this study is the transcribed arguments from a shortened Youtube video by LiveMedia through this link https://www.youtube.com/watch?v=tngaDNSlCpU. When a categorical technique based on Appraisal theory proposed by Martin and White (2005) was applied, the results indicate that they are Mono-glossic-Engagement (79.24%), Hetero-glossic-Engagement (20.76%); Affect-Attitude (6.66%), Judgement-Attitude (66.67%) and Appreciation-Attitude (26.67%); Force-Graduation (90%) and Focus-Graduation (10%). Based on the analysis of Appraisal System, the debating community may accept Bo Seo’s argument about the global poverty pursuing Marxist revolution. Key words: Appraisal theory, Argument, Debate, Bo Seo, WUDC